Can pancreatic steatosis affect exocrine functions of pancreas? - Tahtacı, Mustafa; Algın, Oktay; Karakan, Tarkan; Tayfur Yürekli, Öykü; Alışık, Murat; Köseoğlu, Hüseyin; Ruşen Metin, Melike; Demirezer Bolat, Aylin; Erel, Özcan; Ersoy, Osman (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Pancreatic steatosis (PS) is a generally used term to define accumulation of fat in the pancreas. In theory PS may be able to affect the exocrine function of pancreas. In this study we aimed to determine the effect of PS on exocrine pancreas function. Materials and Methods: Forty-three patients with PS determined by 3 tesla magnetic resonance imaging (MRI) and 48 patients without PS were included in this study. Patients with PS were classified as group 1 and control patients were classified as group 2. Fecal elastase-1 levels were determined. Fecal elastase-1 levels Results: Fecal elastase-1 levels was significantly lower in group 1 compared to group 2 (319.76±45.7 vs 549.31±69.4, respectively, p=0.003). Proportion of patients with EPI was significantly higher in group 1 than group 2 (35.5% vs 12% p=0.042). There were no significant differences in terms of severity or the anatomic distribution of PS in patients with PS with EPI based on MRI (p=0.052, p=0.198, p=0.405) Conclusion: Current study demonstrates that PS can cause EPI. Cite this article as: Tahtacı M, Algın O, Karakan T, et al. Can pancreatic steatosis affect exocrine functions of pancreas? Turk J Gastroenterol 2018; 29: 588-94.